Current reviews of teaching methods for primary school student with attention deficit hyperactive disorder: a Malaysian case study - Mohd Yusof, A.; Sarojini Daniel, E.G.; Low, W.Y.; Ab. Aziz, K. (2011)
Attention Deficit Hyperactive Disorder known as ADHD has been classified as a learning challenging condition which led to special needs specification in education. Children with ADHD often are inattentive, impulsive, and combination of impulsive and inattentive when in the classrooms. Malaysian education system has been focusing on early intervention for addressing the needs of the children with ADHD. The strategy also includes the integration between special education with the national school curriculum where the students with ADHD are grouped together with the other students. However it was found that they just share the same facilities but the teaching methods used are different. Beyond the national schools system there are also private schools which provide special education for students with ADHD. This study identifies the teaching methods applied in the primary schools, both private and public. The paper observes the teaching methods used and highlights the mismatch between teacher experiences, lesson contents and learning environment of each methods. The benefits and challenges will also be discussed. The paper concludes by proposing an alternative teaching strategy designed for students with ADHD.